METAPHOR IN MEDICAL DISCOURSE - Mukhammadzhonovich, Ganiev Marufjon (FAN, TA’LIM VA AMALIYOT INTEGRATSIYASI, 2022)
The article is devoted to the analysis of the functioning of metaphor in medical discourse. The concepts of medical discourse, metaphorical model in medical discourse and medical metaphor-term are considered. The reasons for the emergence of terms in the language of medicine are analyzed and their connection with the process of metaphorization is traced.